Happiness Index for Human Resource Management Practitioners Associated with the Professional Body - Maleka, Molefe Jonathan; Swarts, Ilze; Mmako, Magdeline (Journal of Economics and Behavioral Studies, 2018)
The study explored the perceptions of human resource management (HRM) practitioners in South Africa, using the following happiness dimensions: positive emotions, job-related wellbeing, affective commitment, employee engagement and distributive justice. The research approach was quantitative, and the research design was descriptive and longitudinal (i.e. over a two-year period). The convenience sampling technique was used to select participants. In 2016, the sample size was 204, and in 2017, the sample size was 76. The data were collected at the conventions hosted by the Institute of People Management (IPM). The major findings were that the majority of the participants were females, were employed on a full-time basis, had degrees, earned R40 000 and above, and were not unionized. Participants rated the positive emotions negatively, suggesting that they were disaffected with their remuneration, and they rated the job-related wellbeing, affective commitment, employee engagement and distributive justice items positively. The implication of this study for policymakers is that they must review their remuneration policy and practices. The implication for managers is that they might struggle to keep HRM practitioners effective, motivated, and having cordial relationships.